IMPLEMENTASI KEBIJAKAN INTENSIF ROLEPLAY CUSTOMER SERVICE DAN PENGARUHNYA TERHADAP KUALITAS PELAYANAN NASABAH DI KANTOR PT. BANK TABUNGAN NEGARA (Persero) Tbk, CABANG BOGOR - Deni Haryanto; Husein Maruapey; Agus Suarman Sudarsa (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine how the implementation of the roleplay policyaffects the quality of customer service at the PT. State Savings Bank BogorBranch. This study uses a quantitative descriptive analysis approach, which isa method that functions to describe or provide an overview of the object understudy through data or samples that have been collected as they are, without analyzing and making generally accepted conclusions. The population in thisstudy was taken from 10 employees and 30 customers, while the researchsample was purposive sampling technique with a total of 40 respondents takenfrom the total sample population. The final result of this study concludes thatfrom the results of data analysis that has been collected through filling outquestionnaires by 40 respondents, the calculation of the data obtained is asfollows: The policy implementation variable shows a tcount value of 0.432which is greater than ttable in accordance with the ttable data in thecalculation data table reliability test in making and determining decisions,with the average value (αlpha = 0.05) as ttable. This value which is counted ina positive value indicates that the policy implementation variable has a directinfluence on service performance. Thus, if the implementation of the policy isimproved it will improve the quality of service at BTN